МЕТОД ВИЗНАЧЕННЯ ВСТАНОВЛЕНОЇ ПОТУЖНОСТІ ЕЛЕКТРОСТАНЦІЙ РОЗПОДІЛЕНОЇ ГЕНЕРАЦІЇ З ВІДНОВЛЮВАНИМИ ДЖЕРЕЛАМИ ЕНЕРГІЇ ТА УСТАНОВКОЮ ЗБЕРІГАННЯ ЕЛЕКТРОЕНЕРГІЇ - Буратинський, І.М.; Запорожець, А.О. (Інститут електродинаміки НАН України, Київ, 2025)
The developed method, which consists in determining the installed power of distributed generation, in particular, a wind power plant, a solar power plant, a standby power plant and the technical parameters of an energy storage system, to ensure the security of the supply of electric energy to local consumers, is given. Achieving a balance between the daily amount of electricity produced by distributed generation and the amount of consumption ensures the determination of excess amounts of electricity, which mainly occur during periods of peak solar radiation and, accordingly, the required capacity of an energy storage system. According to the simulation results, it was determined that with the maximum daily consumption of electricity by local consumers during the year at the level of 96 MWh, the daily balance of electricity is achieved at the installed capacity of the wind power plant at the level of 3.6 MW; solar power plant is 14 MW; standby power plant is 3.7 MW and the nominal power of an four-hour energy storage system is 16 MW. References 3,  figures 2, table 1.